Small-Dense LDL, HDL2, 3 - Hirano, Tsutomu (Rinsho byori. The Japanese journal of clinical pathology, 2016)
Low-density lipoprotein (LDL), an established atherogenic lipoprotein, can be fractionated into large buoy- ant (b) and small-dense (sd) particles based on their size and density. An abundance of clinical evidence has shown that sdLDL particles are more atherogenic than lbLDL particles, and the predominance of sdLDL is associated with a three-fold increased risk of coronary artery diseases (CAD). The sdLDL particle is a good substrate for oxidized LDL in the arterial wall. The LDL size is inversely regulated by serum levels of triglycerides (TG) and insulin resistance. Therefore, the level of sdLDL particles is increased in subjects with hypertriglyceridemia, metabolic syndrome, and type 2 diabetes. We established a simple precipitation assay and a homogenous assay for direct measurement of the sdLDL-cholesterol (C) concentration in serum or plasma. Our direct sdLDL assays have been adopted in well-known large cohort studies, and revealed that sdLDL-C more sensitively predicted CAD events than LDL-C or IbLDL-C levels. HDL also has subspecies, namely HDL2 and HDL3. Large cholesterol-rich HDL2 is inversely associated with plasma TG and insulin resistance, whereas small cholesterol-poor HDL3 is not. We established a sim- ple precipitation assay and a homogenous assay for direct measurement of the HDL3-C concentration in se- rum or plasma, which yields HDL2-C by subtracting HDL3-C from HDL-C. The clinical significance of HDL subspecies remains poorly understood, and so should be a subject of further clinical studies. [Review].